1995
DOI: 10.1097/00000658-199509000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Who Would Have Thought It? An Operation Proves to Be the Most Effective Therapy for Adult-Onset Diabetes Mellitus

Abstract: ObjectiveThis report documents that the gastric bypass operation provides long-term control for obesity and diabetes. Summary Background DataObesity and diabetes, both notoriously resistant to medical therapy, continue to be two of our most common and serious diseases. MethodsOver the last 14 years, 608 morbidly obese patients underwent gastric bypass, an operation that restricts caloric intake by (1) reducing the functional stomach to approximately 30 mL, (2) delaying gastric emptying with a c. 0.8 to 1.0 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
1,160
4
89

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,083 publications
(1,308 citation statements)
references
References 19 publications
55
1,160
4
89
Order By: Relevance
“…In 1995, Pories et al 4 reported long term results from 608 severely obese patients who underwent gastric bypass, with a 93% follow-up rate over 14 years. Beyond achieving substantial, durable weight loss (37% of total body weight at 1 year and 30% at 14 years), these individuals experienced remarkable remission of T2DM.…”
Section: Remission Of Diabetes After Rygbmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1995, Pories et al 4 reported long term results from 608 severely obese patients who underwent gastric bypass, with a 93% follow-up rate over 14 years. Beyond achieving substantial, durable weight loss (37% of total body weight at 1 year and 30% at 14 years), these individuals experienced remarkable remission of T2DM.…”
Section: Remission Of Diabetes After Rygbmentioning
confidence: 99%
“…4,5 In the landmark study, by Schauer et al 5 of 1160 patients undergoing RYGB, among the 240 with T2DM severe enough to be treated with oral medications and/or insulin, 30% were discharged from their initial surgical hospitalization with normal plasma glucose levels off all diabetes medicinesFafter an average hospital stay of only 2.8 days. Most of the remainder discontinued their diabetes treatments within a few weeks, and the eventual complete remission rate was 83%.…”
Section: Mechanisms Of Diabetes Improvement Following Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of large numbers of gastric-bypass cases show that on average, patients lose B35% of their pre-surgery body weight within the initial year and that 10 years post-surgery, the majority of the lost weight is not regained. 2,3 Recent attention to the factors contributing to the efficacy of bypass surgery focuses on the combination of increased circulating levels of the distal gut hormones glucagon-like peptide-1 (GLP-1) and peptide YY 3-36, as well as on the reduced stimulation of the 'bypassed' stomach and duodenum as causal in the clinical outcomes. Further support for the contribution of GI signals and their CNS-mediated effects to the physiological control of energy balance comes from the recent success of the GLP-1 analog, exendin-4 (Ex-4), a modified peptidaseresistant GLP-1 analog, in the treatment of type 2 diabetes and from the indications that this treatment also results in body weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of bariatric surgery for the treatment of T2DM started from the report by Pories et al. in 1995 82. Strong evidence has shown that bariatric surgery is an effective treatment for severe obesity (BMI >35 kg/m 2 ) and results in marked improvement of T2DM control 10, 83, 84.…”
Section: From Bariatric To Metabolic Surgerymentioning
confidence: 99%